If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + -7x = -7 + -6 Combine like terms: x + -7x = -6x -6x = -7 + -6 Combine like terms: -7 + -6 = -13 -6x = -13 Solving -6x = -13 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Divide each side by '-6'. x = 2.166666667 Simplifying x = 2.166666667
| 6-2[-4(2-7)-3(2-3)]= | | (x-4)(4x+5)=0 | | 121x^2-25=0 | | 2x+6=4x+6 | | 3x^2+8x+3=0 | | 3-7[7-(9y-4)]= | | 6x+5y=110000 | | 7=-4t | | 7(5y-4)+2(4y+6)= | | 7(5y-6)+2(4y+6)= | | 2-14=-8t+4t | | 5x^2+11x-66=0 | | 5(y*2-4)=-21y | | 6x^2+x=2 | | 6t*2=7 | | s*2-9=0 | | 4(6x-9)=3(12x-8) | | 6z-5=7z-7 | | 6(y+1)-5=7 | | 7-z=3+z+4-2z | | 2u=u-6 | | 8x-4=(2x+1) | | 2x^2+3y^2-30=0 | | 2w+3=7w+13 | | 4y^2+11y+7=5 | | 5y-8=3y+5 | | 4x-3x-7=6x | | 22-3(c-1)=-3c+25 | | 4k^2+6k-1=0 | | 4x-32=2x | | 2(n-1)=8n-3 | | 6x-1=25 |